Mental Health and Criminal Justice: Challenges, Interventions, and Policy Implications - Sulaiman, Shahid; Radhika, M. (International Journal of Criminology and Sociology, 2026)
This study explores the relationship between mental health disorders and criminal behavior, with particular emphasis on the challenges faced by the criminal justice system in managing individuals with psychiatric conditions. Using secondary data derived from peer-reviewed literature, government publications, institutional reports, and case studies, the research examines the prevalence of mental illness among incarcerated individuals, probationers, and offenders under community supervision. The findings reveal that mental health disorders are significantly over represented within correctional populations and are frequently associated with substance abuse, social disadvantage, repeated offending, and poor rehabilitation outcomes. The study further identifies major systemic and institutional barriers, including inadequate mental health training among law enforcement personnel, shortages of qualified mental health professionals, overcrowded correctional facilities, insufficient rehabilitation resources, and delays in psychiatric assessment and treatment. Existing interventions such as mental health courts, crisis intervention teams, counseling services, and community-based rehabilitation programs have shown positive outcomes in reducing recidivism and improving offender reintegration; however, their accessibility and implementation remain inconsistent across jurisdictions. The study concludes that strengthening mental health care within the criminal justice system requires comprehensive policy reforms, improved inter-agency coordination, specialized training for criminal justice personnel, and expanded access to evidence-based and community-centered treatment programs. Addressing these challenges is essential for enhancing rehabilitation outcomes, reducing recidivism, and promoting long-term public safety.